Interacción planta-colibrí en amacayacu (Amazonas, Colombia): una perspectiva palinológica (2001)
From a palinological perspective was studied the plant-hummingbird relationship at community level, in the National Natural Park Amacayacu in the Colombian Amazonia. Our goal was to evaluate the utility ofthe palinological tool, to provided insight of the hummingbird-plant relationship organization, at community leve!. We get evidence about which plants were really using the hummingbirds as pollen vectors. A Resource Importance Value Index (RIVI) is proposed here to evaluate the importance of each floral resource to the hummingbird community. A binary correspondence analysis perrnitted us to proposed three groups ofplant-hummingbird associations, according with the frequency of pollen registered on each hummingbird species. The Relación colibrí-flor en una comunidad amazónica hummingbirds culmen morphology emerged as the explicative factor ofthe associations. The possible role ofthe reticulate pollen sculpture in the syndrome of ornithophily is discussed, as the restrictions and goodness of both methods: palynological and observational .